The Influence of Perceived Organizational Support on Police Job Burnout: A Moderated Mediation Model - Zeng, Xiaoqing; Zhang, Xinxin; Chen, Meirong; Liu, Jianping; Wu, Chunmiao (Frontiers in Psychology, 2020)
Abstract Objective: Based on the theory of perceived organizational support (POS), conservation of resource (COR) and job demands-resources (JD-R) model, this study establishes a moderated mediation model to test the role of job satisfaction in mediating the relationship between perceived organizational support and job burnout, as well as the role of regulatory emotional self-efficacy in moderating the above mediating process. Method: A total of 784 police officers were surveyed with the Perceived Organizational Support Scale, the Job Burnout Questionnaire, the Regulatory Emotional Self-Efficacy Scale, and the Minnesota Job Satisfaction Questionnaire. Results: (1) After controlling for gender, seniority, age, police classification, education, and marital status, regression analysis showed a significant negative correlation between perceived organizational support and burnout (r = -0.42, p < 0.01), and the former had a significant negative predictive effect on job burnout (β = -0.42, p < 0.001). (2) The mediating effect test shows that job satisfaction plays a partial role in mediating the relationship between perceived organizational support and job burnout. (3) Through the analysis of the moderated mediation model test, regulatory emotional self-efficacy moderates the first half of the path of “perceived organizational support → job satisfaction → job burnout". Conclusion: Perceived organizational support not only directly affects police job burnout but also indirectly affects police job burnout through job satisfaction. Regulatory emotional self-efficacy enhances the influence of organizational support on job satisfaction. This study indicates the combined effect of perceived organizational support, job satisfaction and regulatory emotional self-efficacy on job burnout and has certain guiding significance for alleviating police job burnout. Keywords: Perceived organizational support, Job burnout, Job satisfaction, Regulatory emotional self-efficacy, Moderated mediation